Low-Risk Gestational Trophoblastic Neoplasia in Manitoba: Experience With Alternating Methotrexate and Dactinomycin. Issue 8 (October 2018) - Carlson, Vanessa; Walters, Leslea; Lambert, Pascal; Dean, Erin; Lotocki, Robert; Altman, Alon D.
Abstract : Objectives: The aim of this study was to review the treatment and outcomes of low-risk gestational trophoblastic neoplasia (GTN) in Manitoba over more than 3 decades, with a focus on those treated with alternating methotrexate and dactinomycin, a protocol that has only rarely been described. Materials and Methods: We retrospectively reviewed all patients with GTN referred to CancerCare Manitoba from January 1977 to December 2012. Cases were classified as low risk as per the modified WHO-FIGO prognostic scoring system (score, ⩽6). Demographic, treatment, and outcomes data were abstracted, and descriptive statistics and time-to-event analysis were performed. The low-risk protocol used at CancerCare Manitoba consists of alternating single-agent use of methotrexate and dactinomycin, each for 5 days, on a 14-day cycle. Results: Sixty-seven cases of GTN were identified, of which 52 were low risk. Thirty-nine patients were initiated on alternating methotrexate and dactinomycin. Thirty-four (87.2%) achieved primary cure on this regimen, with a median of 4.4 cycles administered (range, 2–7). Median time to response was 56 days. One patient achieved cure after receiving a repeat course of methotrexate as their final cycle. Second-line multiagent chemotherapy was required by 4 patients. Two patients experienced grade 3 toxicities, and none greater than grade 3. There were no recurrences. Conclusions: Alternating methotrexate and dactinomycin is an effective treatment protocol for low-risk GTN, with high rates of primary cure and acceptable toxicity.